Conductivity Studies on Chitosan/PEO Blends with LiTFSI Salt - N. H. Idris; S. R. Majid; A. S. A. Khiar; M. F. Hassan; A. K. Arof (Springer-Verlag, 2024)
Chitosan/PEO-LiTFSI films have been prepared by the solution cast technique. The highest conductivity at room temperature was 1.4 x 10?6 Scm?1 and the activation energy was 0.47 eV for chitosan/PEO blends containing 30 wt.% LiTFSI salts. The conductivity of the samples is dependent on the number of mobile ions.